Organisational citizenship behaviour’s antecedents as predictors of job satisfaction: empirical evidence from banks in emerging economies - Gabriel Maibvisira; Emmanuel Mutambara; Cynthia Mashia (Virtus InterPress, 2022)
It was imperative to determine the impact of antecedents of organisational citizenship behaviour of altruism and conscientiousness on job satisfaction in the banking sector since this strategic sector has been experiencing employee job dissatisfaction-related challenges as evidenced by high staff turnover. The reviewed literature focused on the effect of Organ’s (1998) organizational citizenship behavior (OCB) dimensions of altruism and conscientiousness and employee job satisfaction. The article adopted a positivist philosophy and the explanatory research design since it sought to establish cause and effect relationships between the two constructs. The target population was 150 and a sample of 109 participants was used. A simple random sampling technique was used to select study participants. A Likert scale questionnaire was employed to collect data electronically due to the COVID-19 pandemic movement restrictions. The study findings were that both altruism and conscientiousness have a positive and significant impact on job satisfaction in the banking sector. Thus, it was recommended that the banking sector should create workplace environments that foster OCB to enhance employee job satisfaction. This study was critical since banks are a strategic sector (Bonga, Chirenje, & Mugayi, 2019), particularly in emerging economies as providers of start-up and working capital to both public and private organisations.